Una proposta di criteri per l'edizione di carteggi rinascimentali italiani (Quaderni di Gargnano, 2018)
The essay proposes transcription criteria to be used for Italian letters of the Renaissance period, and marshals a large number of texts to its purpose. The proposal rests on two recent events: the publication of all Baldassarre Castiglione’s letters (1790 texts, Einaudi, 2016) and, as part of a project with Daniela Ferrari, the development of criteria for the transcription of digital photos of the letters of Isabella d'Este, which are available on the "IDEA" platform (i.e. the Isabella D'Este Archive containing digital images of 15000 of her letters , now housed in the Gonzaga Archives of the State Archives of Mantua). The paper reflects on aspects of paper and digital publishing, and shows how a single method of textual interpretation can prove useful for academics from various fields of study. The paper also suggests some solutions for building a critical apparatus, an index and, especially, a glossary when producing a critical edition of these courtly sixteenth-century Italian texts whose wealth of vocabulary merits close lexicographical analysis and commentary.
Keywords: Baldassarre Castiglione; Il libro del cortegiano; Isabella d’Este Gonzaga; Lingua ed Epistolografia cortigiana; Epistolografia del Rinascimento; Filologia e Critica testuale; Criteri di Trascrizione; Storia della Lingua Italiana